Evaluation of Fibular Fracture Type vs Location of Tibial Fixation of Pilon Fractures. (June 2017) - Busel, Gennadiy A.; Watson, J. Tracy; Israel, Heidi
Background: Comminuted fibular fractures can occur with pilon fractures as a result of valgus stress. Transverse fibular fractures can occur with varus deformation. No definitive guide for determining the proper location of tibial fixation exists. The purpose of this study was to identify optimal plate location for fixation of pilon fractures based on the orientation of the fibular fracture. Methods: One hundred two patients with 103 pilon fractures were identified who were definitively treated at our institution from 2004 to 2013. Pilon fractures were classified using the AO/OTA classification and included 43-A through 43-C fractures. Inclusion criteria were age of at least 18 years, associated fibular fracture, and definitive tibial plating. Patients were grouped based on the fibular component fracture type (comminuted vs transverse), and the location of plate fixation (medial vs lateral) was noted. Radiographic outcomes were assessed for mechanical failures. Results: Forty fractures were a result of varus force as evidenced by transverse fracture of the fibula and 63 were due to valgus force with a comminuted fibula. For the transverse fibula group, 14.3% mechanical complications were noted for medially placed plate vs 80% for lateral plating ( P = .006). For the comminuted fibular group, 36.4% of medially placed plates demonstrated mechanical complications vs 16.7% for laterally based plates ( P = .156). Time to weight bearing as tolerated was also noted to be significant between groups plated medially and laterally for the comminuted group ( P = .013). Conclusions: Correctly assessing the fibular component for pilon fractures provides valuable information regarding deforming forces. To limit mechanical complications, tibial plates should be applied in such a way as to resist the original deforming forces. Level of Evidence: Level III, comparative study.